2022
DOI: 10.1002/alz.12708
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic multimorbidity accelerates cognitive decline and dementia progression

Abstract: Introduction: Cardiometabolic diseases (CMDs) have been individually associated with adverse cognitive outcomes, but their combined effect has not been investigated. Methods:A total of 2577 dementia-free participants 60 years of age or older were followed for 12 years to observe changes in cognitive function and to detect incident cognitive impairment, no dementia (CIND) and dementia. CMDs (including type 2 diabetes, heart disease, and stroke) were assessed at baseline through medical records and clinical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…Second, the presence or absence of other comorbid diseases or risk factors is another crucial factor in the association between T2DM and AD. Prior research has revealed that comorbid cardiometabolic disease (including type 2 diabetes, heart disease, and stroke) multimorbidity increased the risk of both MCI and all-cause dementia [29][30][31][32]; this is consistent with our results in this study. Other studies suggested that comorbidity burden (ac- fect the brain's energy supply and metabolism, and APOE is also a metabolism-related protein.…”
Section: Discussionsupporting
confidence: 93%
“…Second, the presence or absence of other comorbid diseases or risk factors is another crucial factor in the association between T2DM and AD. Prior research has revealed that comorbid cardiometabolic disease (including type 2 diabetes, heart disease, and stroke) multimorbidity increased the risk of both MCI and all-cause dementia [29][30][31][32]; this is consistent with our results in this study. Other studies suggested that comorbidity burden (ac- fect the brain's energy supply and metabolism, and APOE is also a metabolism-related protein.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding comparisons between the three distinct trajectory groups, our study found that those diagnosed with hypertension, stroke, coronary heart disease, heart failure, and chronic obstructive pulmonary disease had increased odds for being classified into the high- and moderate-incidence groups. The findings of the current study are comparable to those of previous studies [ 22 , 23 , 24 , 25 ]. These cardiovascular diseases may cause physical disability and cognitive impairment in older adults [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…These cardiovascular diseases may cause physical disability and cognitive impairment in older adults [ 22 ]. Moreover, accelerated cognitive decline and progression of dementia might be independently enhanced by cardiometabolic multimorbidity [ 23 , 24 , 25 ]. In addition, chronic obstructive pulmonary disease can be used as a surrogate marker for smoking behavior [ 26 ], which also has an impact on cognitive functioning [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…T2D, 27 HD, 28 , 29 and stroke 30 are widely recognized dementia risk factors, but only recently has the combined impact of multiple CMDs on dementia risk been explored. Previous studies from our group have shown that the risk of both cognitive impairment 8 and dementia 7 increases with a growing number of co-morbid CMDs (including T2D, HD, and stroke), using data from the Swedish National Study on Aging and Care—Kungsholmen (SNAC-K). In line with this, a recent study using data from the UK Biobank also reported a monotonic increase in dementia risk with one, two, and three co-morbid CMDs (including T2D, myocardial infarction, and stroke).…”
Section: Discussionmentioning
confidence: 99%